Cognitive influence of work-overload and role-conflict on technical education university lecturer’s satisfaction and performance in South-West Nigeria - Aderinto, Idowu Dare; Lemo, Olusiji Olaseni; Shodeinde, Abidemi Olufemi (INVOTEC, 2024)
The productivity of any business is heavily relied on its personnel and their well-being which may influence how satisfied and productive they are. Hence, this study investigated cognitive influences of work-overload and role-conflict on technical education university lecturer’s satisfaction and performance in South-west Nigeria. Descriptive survey research design was adopted for the study. The study was guided by three research questions and two hypotheses. Adapted scales were employed for data collection with an overall reliability coefficient of .90. population for the study comprised all technical education university lecturers in Nigeria. Data was analyzed using mean and standard deviation, Correlation matrix (Pearson Product Moment Correlation), and multiple regression. Findings revealed that there is no significant relationship among work-overload, role-conflict, job satisfaction and performance of technical education university lecturers. Study also revealed significant influence of work-overload and role-conflict on job satisfaction (β= .101; β= -.134; p˃0.05) and performance (β= -.107; β= .076; p˃0.05) among technical education university lecturers. It was concluded and recommended that work-overload and role conflict are significant factors that contributes immensely in affecting satisfaction and overall performance of lecturers on their job. Therefore, efficient training on task management and scheduling should be regularly given to lecturers to alleviate job-strain